Chapter 1 The International Classroom Lexicon Project - Mesiti, Carmel (Taylor & Francis, 2021)
The International Classroom Lexicon Project set out to document the professional vocabulary of middle-school mathematics teachers in ten communities from around the world. The construction of a national lexicon, which can be thought of as the characterisation of a very specific aspect of the culture of each participating country, was undertaken by research teams involving experienced teachers as genuine co-researchers. Each cultural artefact identified the words by which teachers name the classroom phenomena in their respective environment. These are the terms that are used for seeing, describing, and communicating about the world that is the middle-school mathematics classroom.